The use of effector gene based-markers to facilitate identification of Fusarium sp. infected shallot in Java, Indonesia - Lina Herlina; BONJOK ISTIAJI (Society for Indonesian Biodiversity, 2020)
Abstract. Herlina L, Istiaji B. 2020. The use of effector gene based-markers to facilitate identification of Fusarium sp. infected shallot in Java, Indonesia. Biodiversitas 21: 4677-4685. One of the most important diseases and become challenge in breeding resistant variety of shallots in Indonesia is Fusarium disease, caused by Fusarium oxysporum f.sp. cepae (FOC). To discriminate the F. oxysporum into forma speciales is uneasy, often managed through laborious and time-intensive disease assays., therefore molecular approaches become the most relevant choice. FOCs from Indonesia were examined by molecular criteria based on putative and effector genes-based markers, i.e.: SIX-genes, C5-gene, and CRX1-2-genes. The alignment analysis discovered some regions which sequences highly contained conserved bases, while amplification result bands vary in size, between 400 - 500 bp. The combined of 7 SIX-genes primers and 3 effector primers (C5 and CRX1-2) used in the clustering analysis of 15 FOC isolates in this study showed that they succeeded in separating 15 FOC isolates into 4 groups through NTSys. Clustering analysis showed that those markers succeeded in grouping 15 FOC isolates into different clades (by coefficient of similarity: 0.69). Phylogenetic analysis based on CRX genes sequence as putative effector genes confirmed that  CRX1 and CRX2 genes were able to classify the FOC into their forma speciales. Those effectors genes are potential to serve as marker-templates to facilitate identification of FOC which infested shallots in Indonesia.